2015
DOI: 10.1128/jcm.02161-15
|View full text |Cite|
|
Sign up to set email alerts
|

A Stewardship Approach To Optimize Antimicrobial Therapy through Use of a Rapid Microarray Assay on Blood Cultures Positive for Gram-Negative Bacteria

Abstract: A Gram-negative (GN) blood culture microarray assay with an antimicrobial stewardship program (ASP) intervention was evaluated in 126 patients with GN bacteremia. The median time to optimal therapy was shorter in the postintervention group than in the preintervention group (49.3 h versus 38.5 h, respectively; P ‫؍‬ 0.0199). ASP can utilize microarray technology to decrease the time to optimal antimicrobial therapy. The treatment of Gram-negative bloodstream infections (GN-BSI) is particularly complicated due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Despite having the ability to obtain blood culture results up to 1.5 days faster than traditional identification methods, this study shows that without real-time AMS intervention, treatment optimization was significantly delayed. Several studies have established that the use of mRDT in settings with ASPs and microbiology result analysis improves the time to antimicrobial streamlining and various patient outcomes compared to traditional methods of organism identification (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Despite having the ability to obtain blood culture results up to 1.5 days faster than traditional identification methods, this study shows that without real-time AMS intervention, treatment optimization was significantly delayed. Several studies have established that the use of mRDT in settings with ASPs and microbiology result analysis improves the time to antimicrobial streamlining and various patient outcomes compared to traditional methods of organism identification (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value of negative bla CTX-M for susceptibility to third-generation cephalosporins can be examined by clinical laboratories that use this panel and can potentially be exploited to help guide therapy (47). Studies have found that compounded with antimicrobial stewardship, the BC-GN panel can help decrease time to optimal therapy by 11-14 h but vary in findings terms of effect on length of stay or hospital costs (12,48,49).…”
Section: Rapid Molecular Diagnostics For Blood Culturesmentioning
confidence: 99%
“…Initially, studies focused on gram‐positive infections, but now rapid diagnostic technology has expanded to include gram‐negative infections. Studies examining the outcomes of rapid diagnostics for gram‐negative infections have demonstrated various benefits, including faster identification time, improved time to effective antibiotic therapy, decreased length of stay (LOS), and lower costs …”
Section: Introductionmentioning
confidence: 99%
“…1 Initially, studies focused on gram-positive infections, but now rapid diagnostic technology has expanded to include gram-negative infections. Studies examining the outcomes of rapid diagnostics for gram-negative infections have demonstrated various benefits, including faster identification time, 2,3 improved time to effective antibiotic therapy, [4][5][6] decreased length of stay (LOS), [5][6][7] and lower costs. 7 The Verigene gram-negative blood culture (BC-GN) test (Luminex, Austin, Texas) is an automated molecular assay that detects 4 gramnegative species (Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, and Pseudomonas aeruginosa) and 4 gram-negative genera (Acinetobacter, Citrobacter, Enterobacter, and Proteus species) within 2 hours of positive blood culture media.…”
Section: Introductionmentioning
confidence: 99%